Developing The Strategy for Steel Sales by Scenario Planning Approach - Hamonangan Simatupang, Tumpal; Sunitiyoso, Yos (Riviera Publishing, 2023)
The steel industry, often regarded as the mother of industry, holds a pivotal role in fostering national economic independence and supporting vital infrastructure projects. In Indonesia, the development of the steel industry stands as a key indicator of industrial advancement. However, the landscape has evolved dramatically, with escalating competition not just from PT Krakatau Steel but also from numerous emerging competitors producing similar products. This dynamic situation demands an aggressive sales strategy to secure market dominance, especially given the challenges posed by both local and international competitors. Addressing this, PT Krakatau Steel faces the essential question of how to optimize steel sales, approaching or even matching the plant's installed capacity, amidst this competitive environment. The solution lies in proactive strategic planning, which involves a meticulous analysis of both external and internal factors. Recognizing the need for foresight, the company has employed scenario planning, envisioning potential futures for the steel industry. By considering variables like raw material prices and government policies, four scenarios emerged: Armageddon, The King, The King's Speech, and Cast Away. Each scenario prompts a specific set of strategies and actions. Moreover, the company has established early warning systems to discern which scenario might unfold, enabling timely and precise responses. This forward-thinking approach culminated in a comprehensive strategic plan designed to guide PT Krakatau Steel through the complexities and uncertainties of the business landscape over the next seven years.